Evidence for a Sensitive Period for Acculturation - Cheung, Benjamin Y.; Chudek, Maciej; Heine, Steven J. (Psychological Science, 2011)
Though recent adult immigrants often seem less acculturated to their new society than people who immigrated as children, it is not clear whether this difference is driven by duration of exposure or exposure during a sensitive developmental period. In a study aimed at disambiguating these influences, community and student samples of Hong Kong immigrants to Vancouver, Canada, completed the Vancouver Index of Acculturation, a measure that assesses respondents’ identification with their mainstream and heritage cultures. A longer duration of exposure was found to be associated with greater identification with Canadian culture only at younger ages of immigration, but not at later ages of immigration. Conversely, identification with Chinese culture was unaffected by either age of immigration or length of exposure to Canadian culture. These findings provide evidence for a sensitive period for acculturation: People are better able to identify with a host culture the longer their exposure to it, but only if this exposure occurs when they are relatively young.